$ax^2+bx+c = 0$ is a quadratic equation in general form. One root is twice the other root.

01

Assume, $\alpha$ and $\beta$ are two roots of the quadratic equation. Summation and product of the both roots are,

$\alpha + \beta = -\dfrac{b}{a}$

$\alpha \beta = \dfrac{c}{a}$

02

It is given that one root is twice the second root. So, $\beta = 2 \alpha$. Now, eliminate $\beta$ from both roots relations by using this condition.

$\alpha + \beta = -\dfrac{b}{a}$

$\implies \alpha + 2\alpha = -\dfrac{b}{a}$

$\implies 3\alpha = -\dfrac{b}{a}$

$\therefore \,\, \alpha = -\dfrac{b}{3a}$

$\alpha \beta = \dfrac{c}{a}$

$\implies \alpha \times 2 \alpha = \dfrac{c}{a}$

$\implies 2 \alpha^2 = \dfrac{c}{a}$

$\therefore \,\, \alpha^2 = \dfrac{c}{2a}$

03

Now, replace the value of $\alpha$, obtained from the summation of the roots of the quadratic equation.

$\implies {\Bigg(-\dfrac{b}{3a}\Bigg)}^2 = \dfrac{c}{2a}$

$\implies \dfrac{b^2}{9a^2} = \dfrac{c}{2a}$

$\implies 2a \times b^2 = 9a^2 \times c$

$\implies 2ab^2 = 9a^2c$

$\require{cancel} \implies 2\cancel{a}b^2 = 9\cancel{a^2}c$

$\implies 2b^2 = 9ac$

$\therefore \,\,\,\,\,\, \dfrac{b^2}{ac} = \dfrac{9}{2} = 4.5$

Therefore, it is the required solution for this quadratic equation.

Latest Math Topics

Latest Math Problems

A best free mathematics education website for students, teachers and researchers.

Learn each topic of the mathematics easily with understandable proofs and visual animation graphics.

Learn how to solve the maths problems in different methods with understandable steps.

Copyright © 2012 - 2022 Math Doubts, All Rights Reserved